Sign-changing and multiple solutions for the p-Laplacian - Siegfried Carl; Kanishka Perera (Abstract and Applied Analysis)
We obtain a positive solution, a negative solution, and a sign-changing solution for a class of p-Laplacian problems with jumping nonlinearities using variational and super-subsolution methods.